Pemanfaatan Jaringan Saraf Tiruan Multi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Artificial neural network (ANN) inspired from Biologica] Science. The network had made is require a number of assumption of anatomy and brain function which unlike brain in fact. The main characteristic of artificial neural network its ability to learn. One of artificial neural network type is multilayer perceptron feedforward. This network can be trained to recognize a certain pa ttern_ The pattern of temperature and rainfall is almost equal in specific period in one year. By using multilaver perceptron feedforward neural network, the shifting of temperature and rainfall pattern is adapted so that expected to produce accurate weather prediction.